OPTIMASI FORMULA SEDIAAN SABUN MANDI CAIR DARI EKSTRAK KULIT MANGGIS (Garcinia Mangostana Linn.) - Yunia Irmayanti, Putu; Ayu Dewi Wijayanti, Ni Putu; Istri Sri Arisanti, Cokorda (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 2 Juli 2014, 2014)
Mangosteen rind is a valuable waste, rich in saponins, xanton, and tannin. Liquid soap was made by saponification reaction of ethanol extract of mangosteen rind and fats are reacted with KOH. This study aims to perform the optimization of liquid soap formula and determine its physical and chemical properties. Extract of mangosteen (Garcinia mangostana L.) obtained by maceration for 3 days with 70% ethanol, and vaccuum evaporated. Liquid soap was prepared by heating method for ± 3 hours. The evaluation consists of organoleptic test, pH, and specific gravity determination. The results show that the liquid soap from 2% ethanol extract of mangosteen rind is dark brown, homogenous liquid, has a characteristic odor and specific gravity between 1.022 to 1.036 g / ml, and pH between 12.16 to 12, 92. From the test results, liquid soap formulas which meet commercial criteria are formula V and VI.
Keywords: Mangosteen rind, maceration, liquid soap, optimation, optimum formula